Polemics and persecution: East Romans and Paulicians c.780-880) - Dixon, Carl Stephen (2018)
Paulicians represent one of the most dynamic religious and military phenomena in the eastern Mediterranean during the ninth century. Despite being unknown to Greek sources at the beginning of this century, Paulicians were persecuted by the East Roman Empire in the 810s and again in the 840s. After this later persecution, they aligned themselves with the Emirate of Malaṭiya and raided the empire’s eastern provinces until their eclipse as a regional power in the 870s. Yet modern scholarship concerning Paulicians has conventionally focused on their religiosity, which has traditionally been identified as a variant of adoptionism descended from primordial forms of Armenian Christianity, and/or as a Manichaean or Marcionite dualism which would influence later heresies in Bulgaria and the Languedoc. In contrast to approaches such as these, which locate Paulicians within broader religious metanarratives, this thesis seeks to analyse Paulician religiosity on its own terms by grounding it within its social, religious and politico-military contexts. In doing so, it will reappraise Paulician activity after a comparative dearth of scholarly interest lasting several decades.